Influence of Narrative and Dramatized Political Content on 2024 Regional Election Participation - Setyani Utami; Wahid, Umaimah (Communicare : Journal of Communication Studies, 2024)
This study aims to examine the influence of narrative and dramatization in political content on public political participation in the 2024 Simultaneous Regional Election (Pilkada) in Barito Timur Regency. A quantitative approach was used, with survey questionnaires distributed to 100 respondents from various demographic groups. The data were analyzed using descriptive statistics and multiple regression analysis. The findings reveal that both narrative and dramatization in political content significantly affect political participation. Specifically, political narratives that resonate with local issues and emotionally charged dramatization elements encourage individuals to engage in political discussions and voting activities. This study contributes to the field of political communication by highlighting the role of media content in shaping political behavior. The practical implications are crucial for political campaign strategies, especially in utilizing social media platforms to influence voter engagement. The results also offer insights for further research on the impact of digital media content on political participation in contemporary electoral processes.